LOGISTICS AND COLD CHAIN RELATIONSHIP - Seprényi, Kitti; Tamás, Péter; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2022)
The emergence of vaccines to contain and defeat the now-famous virus has been a huge step forward for mankind, but how and under what conditions these vaccines can get from the place of production to the place of use has been a major challenge. Whether in packaging or transport, there are stringent requirements to be met and COVID-19 vaccines have different cold chain requirements depending on the type of vaccine, its thermal stability, its current condition, and its shelf life at different storage temperatures. Currently, one vaccine must be stored and transported at ultra-low temperature (ULT - Ultra-Low Temperature) between -90°C and -60°C. Effective use of this requires good cold chain planning, efficient management of vaccine supply, logistics and distribution, and strategic deployment of ULT equipment. The pandemic has brought cold chain logistics to the forefront, and in this paper, we examine the relationship between logistics and the cold chain.